Color pattern evolution in Vanessa butterflies (Nymphalidae: Nymphalini): non‐eyespot characters. Issue 1 (January 2015) - Abbasi, Roohollah; Marcus, Jeffrey M.
SUMMARY A phylogenetic approach was used to study color pattern evolution in Vanessa butterflies. Twenty‐four color pattern elements from the Nymphalid ground plan were identified on the dorsal and ventral surfaces of the fore‐ and hind wings. Eyespot characters were excluded and will be examined elsewhere. The evolution of each character was traced over a Bayesian phylogeny of Vanessa reconstructed from 7750 DNA base pairs from 10 genes. Generally, the correspondence between character states on the same surface of the two wings is stronger on the ventral side compared to the dorsal side. The evolution of character states on both sides of a wing correspond with each other in most extant species, but the correspondence between dorsal and ventral character states is much stronger in the forewing than in the hindwing. The dorsal hindwing of many species of Vanessa is covered with an extended Basal Symmetry System and the Discalis I pattern element is highly variable between species, making this wing surface dissimilar to the other wing surfaces. The Basal Symmetry System and Discalis I may contribute to behavioral thermoregulation in Vanessa. Overall, interspecific directional character state evolution of non‐eyespot color patterns is relatively rare in Vanessa, with a majority of color pattern elements showing non‐variable, non‐directional, or ambiguous character state evolution. The ease with which the development of color patterns can be modified, including character state reversals, has likely made important contributions to the production of color pattern diversity in Vanessa and other butterfly groups.